2018
DOI: 10.1097/ftd.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics Evaluation of Mycophenolic Acid and Its Glucuronide Metabolite in Chinese Renal Transplant Recipients Receiving Enteric-Coated Mycophenolate Sodium and Tacrolimus

Abstract: The pharmacokinetic profile of total and free MPA and its main metabolite MPAG was examined in Chinese adult renal transplant patients receiving EC-MPS. The use of LSS to estimate individual free and total MPA exposure could be useful in optimizing patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…MLR is a straightforward technique available with every statistics software program, and the resulting equations can be easily implemented in a spreadsheet. Although for MMF most LSSs of 2-3 time points within the first 3 hours postdose were efficient to approximate the full AUC, 9 for EC-MPS it was not straightforward 148 : 3 blood samples were rarely sufficient 142,146 but more often 4 and up to 8 were required, 149,150 over a generally longer period of 4-9 hours after dosing 146,148,[150][151][152] because of the highly variable absorption of the drug and day-to-day fluctuation in enterohepatic cycling of MPA. 9 Importantly, Hougardy et al 143 reported that MPA AUC estimation using a 4-point LSS failed in .30% of patients on EC-MPS, especially when C0 was the highest concentration measured.…”
Section: Limited Sampling Strategiesmentioning
confidence: 99%
“…MLR is a straightforward technique available with every statistics software program, and the resulting equations can be easily implemented in a spreadsheet. Although for MMF most LSSs of 2-3 time points within the first 3 hours postdose were efficient to approximate the full AUC, 9 for EC-MPS it was not straightforward 148 : 3 blood samples were rarely sufficient 142,146 but more often 4 and up to 8 were required, 149,150 over a generally longer period of 4-9 hours after dosing 146,148,[150][151][152] because of the highly variable absorption of the drug and day-to-day fluctuation in enterohepatic cycling of MPA. 9 Importantly, Hougardy et al 143 reported that MPA AUC estimation using a 4-point LSS failed in .30% of patients on EC-MPS, especially when C0 was the highest concentration measured.…”
Section: Limited Sampling Strategiesmentioning
confidence: 99%
“…Next, the |MPE| percentages within 15% (F 15 ), 20% (F 20 ), and 25% (F 25 ) were calculated. The model was considered clinically acceptable if it yielded an MPE ≤ ±15%, MAE ≤ 30%, F 15 > 40%, F 20 > 45%, and F 25 > 50% [33].…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…The predictive performance was evaluated using the coe cients of determination (R 2 ), mean prediction error (MPE), and mean absolute prediction error (MAE), which were described by Sheiner and Beal 33 |MPE| percentages within 15% (F15), 20% (F20), and 25% (F25) were calculated. The model is considered clinically acceptable if it yields an MPE ≤ ± 15%, MAE ≤ ± 30%, F15 > 40%, F20 > 45%, and F25 > 50% 34 .…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%